1990
DOI: 10.1172/jci114601
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 mRNA is widely expressed in porcine and human tissues.

Abstract: Endothelin-1 (ET-1) is a potent vasoconstrictor peptide isolated from porcine endothelial cells. We have previously demonstrated widespread binding sites for ET-1 in blood vessels, heart, kidney, adrenal, lung, and brain in a distribution that paralleled that of endothelial cells. To determine whether these cells are capable of synthesizing ET-1 in close proximity to its binding sites, amplification of cDNA using the polymerase chain reaction and in situ hybridization were used to study the distribution of ET-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(71 citation statements)
references
References 27 publications
3
68
0
Order By: Relevance
“…ND, not detected. 1988, Bloch et al 1989, MacCumber et al 1989, Matsumoto et al 1989, Arai et al 1990, Nunez et al 1990, Sakurai et al 1990, Firth & Ratcliffe 1992, Shiba et al 1992. However, different analytical methods (Northern blot analysis, RNase protection assay, immunological detection methods, and RT-PCR), different species (rat, human, and pig), and different stages of animal development have been presented in these reports.…”
Section: Discussionmentioning
confidence: 99%
“…ND, not detected. 1988, Bloch et al 1989, MacCumber et al 1989, Matsumoto et al 1989, Arai et al 1990, Nunez et al 1990, Sakurai et al 1990, Firth & Ratcliffe 1992, Shiba et al 1992. However, different analytical methods (Northern blot analysis, RNase protection assay, immunological detection methods, and RT-PCR), different species (rat, human, and pig), and different stages of animal development have been presented in these reports.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was generated using 1/lg of total RNA as a template in the presence of cloned murine Moloney leukemia virus reverse transcriptase and random hexamers. ET-1 primers were designed as 5'-TGC TCC TGC TCT TCC CTG ATG GAT AAA GAG TGT GTC-3" (sense) and 5'-GGT CAC ATA ACG CTC TCT GGA GGG CTT-3' (antisense) [27]. The primers were predicted to amplify a 462 base pair DNA fragment (nucleotides 157 to 618) [2].…”
Section: Reverse Transcription-polymerase Chain Reaction ( Rt-pcr)mentioning
confidence: 99%
“…12 It is also expressed in various other types of cells and organs (such as blood vessels, heart, kidney, adrenal glands, lung and brain) and acts via two types of ET receptors, the ET-A and ET-B receptors, in a paracrine and autocrine manner. 13,14 ET-1 has proliferative properties in smooth muscle cells and also promotes endocrine and metabolic functions, such as aldosterone or cortisol secretion. 14,15 Additionally, it has been shown that ET-1 may stimulate leptin secretion in cultured adipocytes.…”
Section: Introductionmentioning
confidence: 99%